Kreativitas Pengembangan Formula Tempe Generasi Dua Di Kota Malang - Fitriah, Arsinah Habibah; Kristianto, Yohanes; Pudjirahaju, Astutik (Jurnal Informasi Kesehatan Indonesia (JIKI), 2017)
Abstract: This study was aimed to explore second generation tempe consumption pattern of in Malang.This study was descriptive qualitative.Tempeh consumption pattern was obtained from group of motherof 6-59 months child with malnutrition and pregnant withchronic energy deficiency. In general, respondentsconsumed tempeh almost everyday. Tempe products were prepared traditionally in form of snackor protein source side dish. Tempeh processing is generally done by frying. Respondents have recognizedthe new way of processing tempeh in form of second generations. Respondents living in the tempehindustry area usedmore various ingredients and more complex methods of cooking. They also indicatedthe ability to adopt new way of tempeh processing. Conclusion: People in Malang consumes tempeh intwo forms, ie. side dishes and snack traditionally processed mainly by frying. They may adopt new wayof tempeh processing.